A Thought-Provoking Case of Successfully Treated Carcinoma of the Head of the Pancreas with Metachronous Lung Metastasis: Impact of Distal Spleno-Renal Shunt for Regional Invasion on Long-Term Period after Pancreaticoduodenectomy. (29th May 2021) - Aoyama, Ryuhei; Hori, Tomohide; Yamamoto, Hidekazu; Harada, Hideki; Yamamoto, Michihiro; Yamada, Masahiro; Yazawa, Takefumi; Sasaki, Ben; Tani, Masaki; Sato, Asahi; Katsura, Hikotaro; Kamada, Yasuyuki; et al.
Abstract : When performing pancreaticoduodenectomy with resection of the confluence of the superior mesenteric vein and portal vein, division of the splenic vein may cause sinistral portal hypertension resulting in gastrointestinal bleeding, splenic congestion, and hypersplenism. To prevent these adverse events, it is important to intentionally decompress the splenic vein. This report is of a 68-year-old woman with stage IA carcinoma of the head of the pancreas who survived for more than six years following tumor resection and pancreaticoduodenectomy and distal splenorenal shunt. A 68-year-old woman was diagnosed with carcinoma of the head of the pancreas that involved the confluence of the superior mesenteric vein, portal vein, and splenic vein. No unresectable cancer sites or distant metastases were detected. Pancreaticoduodenectomy with resection of the confluence of the superior mesenteric vein and portal vein was performed. The superior mesenteric vein and portal vein were anastomosed in the end-to-end fashion, and the remnant splenic vein was anastomosed to the superior aspect of the left renal vein in the end-to-side fashion. At 22 months after the initial surgery, the patient underwent partial lung resection for a metachronous lung metastasis. For 6 years after the initial surgery, the venous reconstructions have maintained their patency without any obstruction of splenic venous flow, and the patient has remained in good health without further metastases or recurrences. This case has shown the importance of early diagnosis of carcinoma of the head of the pancreas, as appropriate and timely surgical management can result in good outcome. This patient responded well and remains alive six years following pancreaticoduodenectomy and preservation of the spleen with the use of a distal splenorenal shunt.